Job preferences among traditional Chinese medicine clinical graduates in China: a discrete choice experiment - Yichun Gu; Botao Tian; Shang Wu; Shimeng Liu; Lihang Sun; Yaqun Wang; Huaxin Yu; Yulin Zhang; Jinying Su; Da He (BMC Medical Education)
Abstract Background Primary-level Traditional Chinese Medicine (TCM) healthcare institutions are currently facing a severe shortage of TCM professionals, highlighting the urgent need to explore the job preferences of TCM clinical graduates. This study aimed to investigate the stated job preferences of TCM clinical graduates when seeking employment. Methods A discrete choice experiment (DCE) was conducted to assess the employment preferences of TCM clinical graduates from 16 TCM universities across China. The job attributes examined included the monthly income, work location, hospital tier, job stability (position tenure), work intensity, opportunities for mentorship under renowned practitioners, and career advancement prospects. A mixed logit model was employed to obtain the main effects model. Based on the results of the main effects model, analyses of relative importance and willingness to pay (WTP) were conducted. Additionally, heterogeneity analysis and scenario simulation analysis were performed. Results A total of 2,402 valid questionnaires were included in the primary DCE analysis. Monthly income was the most important factor (RIS = 52.58%). Among non-economic factors, participants expressed the strongest willingness to reduce workload, being willing to forgo 2,367.5 yuan in monthly income to transition from high to low work intensity. Other significant factors included formal establishment (RIS = 11.32%), mentorship opportunities (RIS = 7.44%), and hospital level (RIS = 4.63%), with job location being the least important (RIS = 3.44%). Subgroup analysis showed that male graduates were more willing than female graduates to forgo formal establishment for mentorship opportunities. Graduates from the eastern region valued lower work intensity and formal establishment more than those from the central and western regions. Postgraduates were more likely than undergraduates to give up monthly income for jobs in higher-tier cities. Scenario analysis revealed that graduates had a 43.0% probability of choosing third-tier cities under baseline conditions. Comprehensive improvements (e.g., higher income and formal establishment) increased this probability to 84.8%, rising to 87.3% with better promotion opportunities. Conclusion This study demonstrates that the monthly income has the most significant impact on employment preferences. The work intensity and mentorship opportunities also play crucial roles, with the influence of the work intensity surpassing those of other non-economic factors. In contrast, the hospital tier and work location have a relatively smaller impact on graduates’ preferences. In addition, a combination of certain non-economic measures can enhance students’ willingness to choose hospitals in third-tier cities. Based on these findings, it is recommended that recruitment and career development strategies focus on the salary, work intensity, and mentorship opportunities, while providing stable job positions and favorable work environments, so as to meet the primary needs of TCM clinical graduates. A novel contribution of this study is its identification of the significant influence of mentorship opportunities, which are one of the distinctive features of TCM, on the employment choices of TCM graduates, filling a gap in the existing research. Future studies should integrate online questionnaires with offline interviews to gain deeper insights into the decision-making processes of graduates in real-world work environments.